Assessment of the Typification of the Complex Landscape of The Land Areas of The Namangan Adyrs of The Ferghana Valley. Republic Of Uzbekistan. (Texas Journal of Engineering and Technology, 2023)
Namangan adyrs are located in the north-eastern part of the Fergana Valley, with a complex landscape, the development of ravines in ravine-prone areas in the process of ravine erosion, as the channels of water flows deepen, the factor of erosion of the underlying mountain breeds will become increasingly important. Widespread anthropogenic land development in Uzbekistan in 1975-2002 influenced the activation of erosion and man-made soil disturbance, which led to a reduction in more than 300 thousand hectares of agricultural land and a deterioration in the soil - environmental situation of the country. Mapping of ravine erosion in complex landscape conditions in the world practice of erosion, it is customary to map linear forms of ravine erosion by deciphering aerospace photographs, as well as traditional mapping methods using topographic maps. The article provides for the patterns of manifestation of the growth and development of the ravines of the Namangan adyrs, studied linear forms of erosion with the identification of their morphological and morphometric characteristics.